2020
DOI: 10.1002/brb3.1756
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety profile of neuroendoscopic hematoma evacuation combined with intraventricular lavage in severe intraventricular hemorrhage patients

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…One RCT with 81 patients suffering from IVH, evaluated cisternal irrigation with saline and gentamicin during surgery versus trepanation drainage and found a significantly increased rate of favourable outcome (ADL=good/excellent) in patients treated with cisternal irrigation at 3 months after surgery (92.1% vs 82.5%, p<0.01). 35 Another RCT with 21 patients 36 evaluated the effect of intraventricular irrigation using the irrigation system IRRAflow, 37 using a dual-lumen catheter for automatised fluid exchange based on periodic irrigation and aspiration. 38 The study was terminated early, due to safety concerns, 36 as they found that the intervention group had a higher rate of catheter occlusion Cisternal irrigation overall compared with conventional treatment for subarachnoid haemorrhage [13][14][15][16][17][18][19][20][21][22] Mortality…”
Section: Open Access Table 1 Summary Of Findings and Grade Assessmentmentioning
confidence: 99%
“…One RCT with 81 patients suffering from IVH, evaluated cisternal irrigation with saline and gentamicin during surgery versus trepanation drainage and found a significantly increased rate of favourable outcome (ADL=good/excellent) in patients treated with cisternal irrigation at 3 months after surgery (92.1% vs 82.5%, p<0.01). 35 Another RCT with 21 patients 36 evaluated the effect of intraventricular irrigation using the irrigation system IRRAflow, 37 using a dual-lumen catheter for automatised fluid exchange based on periodic irrigation and aspiration. 38 The study was terminated early, due to safety concerns, 36 as they found that the intervention group had a higher rate of catheter occlusion Cisternal irrigation overall compared with conventional treatment for subarachnoid haemorrhage [13][14][15][16][17][18][19][20][21][22] Mortality…”
Section: Open Access Table 1 Summary Of Findings and Grade Assessmentmentioning
confidence: 99%
“…According to the previous study [8] , we de ned postoperative rehemorrhage as an increase in the hematoma volume of more than 33% compared to the previous postoperative CT scan, or reappearance of hyperdensity in the focal region at the follow-up CT scan after it was removed completely. Besides, hematoma clearance rate = (preoperative hematoma volume − postoperative hematoma volume) / preoperative hematoma volume [9] . Diagnoses of in-hospital complications were made by quali ed clinical practitioners according to the relevant guidelines.…”
Section: Data Collection and De Nition Of Variablesmentioning
confidence: 99%